Strong and biocompatible lignin /poly (3-hydroxybutyrate) composite nanofibers. (12th April 2018) - Kai, Dan; Chong, Hui Moon; Chow, Li Ping; Jiang, Lu; Lin, Qianyu; Zhang, Kangyi; Zhang, Huijie; Zhang, Zheng; Loh, Xian Jun
Abstract: Poly(3-hydroxybutyrate) (PHB) is an attractive biopolymer potential for various applications, but its brittle nature is a big handicap. In this study, we proposed lignin copolymers as mechanical reinforcement agents for PHB. A series of lignin copolymers (random and block) were synthesized via the solvent free ring-opening polymerization (ROP) of β-butyrolactone and/or ε-caprolactone onto lignin core. The lignin copolymers were characterized by nuclear magnetic resonance (NMR), gel permeation chromatography (GPC) and differential scanning calorimetry (DSC). Next, these lignin copolymers were incorporated into PHB nanofibers as reinforcement fillers, in order to improve their mechanical properties. It is found that the lignin block copolymer with poly(ε-caprolactone) (PCL) segment followed by PHB segment (LPC + H) displayed the best mechanical improvement. Tensile strength of PHB nanofibers enhanced from 1.81 MPa to 3.13 MPa, and elongation at break increased from 15% of 55%. In the reinforced system, lignin plays as a rigid core, PCL acts a rubbery layer and PHB segment forms strong bonding with fiber matrix. Moreover, PHB/lignin nanofibers were demonstrated with superior biodegradability and biocompatibility, indicating that the new nanofibrous system holds great potential for biomedical applications. Graphical abstract: Image 1 Sustainable lignin-PCL-PHB copolymers, synthesized via ring-opening polymerization, significantly improved the mechanical properties of PHB nanofibers.